Międzygeneracyjna transmisja wartości w firmach rodzinnych w kontekście sukcesji - Trembaczowski, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Family, a primary group, is a natural domain of upbringing in human life. Parents have tremendous influence on the formation of the cognitive framework, beliefs and moral attitudes of their children. They educate them to fulfil various social roles and build their own identity. Values constitute a feature that distinguishes family businesses from other enterprises, and the intergenerational transmission of values becomes a mechanism that allows for generational continuity, leading to a permanent identity of the company.The article is devoted to the problem of values in the context of preparing successors to take managerial and ownership positions in family businesses.The article is anchored theoretically in Pierre Bourdieu’s research position, as well as the concept of symbolic boundaries by Michele Lamont.The article discusses the results of qualitative research carried out in family businesses under succession process.The interviews were conducted with both senior managers and their successors, which enable an effective comparison of the perspectives unveiled by both generations.